Study on the Synthesis and Hypolipidemic Activities of Coumarin Oxime Esters Derivatives - Chang, Haoyun; Li, Guangyao; Liu, Peng; Hu, Supei; Huang, Peng; Hu, Haixia; Xu, Nongzhang; Zhou, Yang (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The major objective of this research was to synthesize and evaluate the hypolipidemic Activities of Coumarin Oxime esters and develop the possible target. Materials and Methods: Using salicylaldehyde and ethyl acetoacetate as raw materials, coumarin-3-carboxylic acid was synthesized by Knoevenagel reaction, and then reacted with hydroxylamine hydrochloride to form oxime, which was then dehydrated and condensed with niacin and acetylsalicylic acid respectively to obtain six coumarin oxime ester target compounds. MS and HNMR were employed to confirm the structures of the examined compounds. The hypolipidemic effect of these compounds was evaluated by experimental mice models. The interaction of small-molecules and possible targets was assessed by Discovery Studio (v4.5). Results: The optimal reaction condition for oxime was as follows: n (3-acetyl coumarin): n (pyridine) = 1:30, the yield was 76.8%. The optimal reaction condition for synthesis oxime ester was as follows: the reaction time was 48 hr, the yield was 57.2%. The results of enzyme immunosorbent assay showed that the substances C1 and C4 both demonstrated specific lipid-lowering properties and were able to considerably decrease the triglyceride and total cholesterol levels in mice. Coumarin oxime nicotinate has a stronger effect on reducing serum triglyceride, while coumarin oxime aspirin has a stronger effect on reducing total cholesterol. The docking result indicated the 3QNT may be the possible hypolipidemic target of C1 with binding energy of -1.65 kcal/mol. Conclusion: It can be concluded that coumarin oxime esters would be carefully explored and developed as hypolipidemic drugs. The future research work should emphasis on the alteration of the coumarin oxime backbone at the mean time keeping the right-hand side of the nicotinic acid and aspirin structures.
Keywords: Coumarin; Oxime esters; Synthesis; Hypolipidemic; Targets